Adoption of certified organic technologies: the case of coffee farming in Colombia - Marcela Ibanez (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
Agricultural production is an important source of income and employment for developing countries, yet it is the cause of serious environmental problems. Though ECO-labels appear as a promising alternative to control the negative effects of agriculture on the environment and to increase the income of rural poor, the proportion of agricultural land and exports certified as is quite small. We investigate the factors that affect the adoption of certified organic coffee in Colombia and in particular study the effect of economic incentives on adoption. We find that those who have lower cost of adoption are more likely to be certified as organic. Correcting for sample selection, we find that certified organic production is 40% less productive and 31% less costly than non-certified production. Given the price premium in 2007, certified organic production is 15% less profitable than non-organic production. We find that in order to make organic production attractive, the price premium of certified organic coffee should be about 5 times higher than in 2007.
Keywords: 330; Technology adoption; Switching regression models; Organic Coffee; Colombia